Connecting Environmental Action to E-participation Design for Young People - Stefano De Paoli; Paula Forbes (JeDEM - eJournal of eDemocracy & Open Government, 2020)
The paper offers a conceptual analysis and a case study research on the design of e-participation in environmental policy-making for young people. This is achieved by connecting the concept of environmental action with e-participation design. Through a literature review, four core dimensions of environmental action for young people are identified: ownership, participation, stakes in the future and experience. Through a case study of research conducted for an applied project aimed at designing and piloting a novel e-participation solution, the paper shows how young people, implicitly see the connections between these four dimensions of environmental action and the e-participation process. The dimensions of environmental action have, then been used as the basis for co-creation activities and for a subsequent evaluation of e-participation. The results support the position that environmental action can underpin the design and can increase e-participation capacity in environmental policy-making for young people.